1989
DOI: 10.2190/hmnx-9v7j-652x-pwj4
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual Syndrome and Locus of Control

Abstract: Seventy-six women completed a three-month prospective evaluation for premenstrual syndrome (PMS). As a part of the evaluation, they completed Rotter's Locus of Control (LOC) form in the follicular phase and premenstrually. It was found that the LOC scores of women meeting criteria for PMS rose significantly (became more "external") premenstrually, while scores of women without PMS did not show significant change. In addition, the premenstrual LOC scores of women meeting criteria for PMS were significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
7
2
Order By: Relevance
“…Although others (O'Boyle, Severino, & Hurt, 1988) have found locus of control to predict severity of premenstrual symptoms, there was no support for our second or fifth hypothesis. Locus of control did not differentiate between mild and strong reports of premenstrual symptoms, nor were those with external LOC more likely to believe that other women could be diagnosed with PMS.…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…Although others (O'Boyle, Severino, & Hurt, 1988) have found locus of control to predict severity of premenstrual symptoms, there was no support for our second or fifth hypothesis. Locus of control did not differentiate between mild and strong reports of premenstrual symptoms, nor were those with external LOC more likely to believe that other women could be diagnosed with PMS.…”
Section: Resultscontrasting
confidence: 95%
“…The fundamental error of attribution and the illusory correlation may explain the tendency of the participants in Koeske & Koeske's (1975) classic study to attribute a vignette character's negative affect to PMS even when the situation was described as unpleasant. Other than a few studies of PMS as a form of self-handicapping (Bates & Beck, 1991;Mello-Goldner & Jackson, 1999) and as predicted by external locus of control (O'Boyle, Severino, & Hurt, 1988), PMS does not seem to have been actively studied by researchers interested in social cognition. The present study represents a preliminary attempt to consider optimism and the false uniqueness effect in relation to personal symptom reports and beliefs about the incidence of severe PMS.…”
mentioning
confidence: 99%
“…This finding contradicts previous studies examining locus of control and PMS (Christensen, Board, & Oei, 1992;Harding, 1989;O'Boyle, Severino & Hurt, 1988). In previous studies, women with PMS were found to have a higher external locus of control than women without PMS.…”
Section: Discussioncontrasting
confidence: 89%
“…The criteria tested were among those that have been used in previous PMS/ LLPDD research (3,6,(8)(9)(10)(11). Specifically, we examined a) 30% change, defined in two ways since both have been used (3-7): 1) a 30% or greater increase in symptoms during the mid-luteal or premenstrual phase compared with the early follicular phase (first four days following cessation of menstrual bleeding), and 2) the difference between the mid-luteal or premenstrual phase and the early follicular phase divided by the actual range of ratings over all cycle days, which we labeled modified 30% change; b) 75% change as defined in a-1) (10); c) an effect size criterion >1, defined as the difference between the mid-luteal or premenstrual phase and the early follicular phase divided by the standard deviation of ratings over all cycle days (9, 10); and d) an absolute severity threshold which required at least one day during the mid-luteal or premenstrual phase when the symptom was rated five or higher on a six-point scale, and not more than one day in which it was rated two or higher during the early follicular phase (8,10,11).…”
Section: Confirmation Of Pms/llpdd: Degree Of Symptom Changementioning
confidence: 99%
“…To be "confirmed" by this criterion, symptom ratings must increase 30% or more during the week prior to menstruation compared with the first week following cessation of menses in at least two consecutive cycles. This guideline has been used more often than any other in studies of PMS over the last decade (3)(4)(5)(6)(7). Concerns have been raised about its appropriateness (8,9), however, and some studies have used other percent change criteria (10), or criteria based on absolute severity thresholds (8,10,11).…”
Section: Introductionmentioning
confidence: 99%